Electrochemical production, characterization, and application of MWCNTs - Aleksandar T. Dimitrov, Ana Tomova, Anita Grozdanov, Orce Popovski, Perica Paunović (Springer, 2013)
The subject of this study is production of carbon nanotubes (CNTs) using an original procedure of reduction of lithium molten salts onto graphite cathode; their structural characterization and application as support material for electrocatalysts aimed for hydrogen evolution. As-produced CNTs were characterized by means of scanning and transmission electron microscopy (SEM and TEM), Raman spectroscopy, and thermogravimetric and differential thermal analysis (DTA). SEM and TEM images have shown that nanotubes are mostly of curved shape with length of 1–20 μm and diameter of 20–40 nm. Raman peaks indicate that the crystallinity of produced nanotubes is rather low. The obtained results suggest that formed product contains up to 80 % multiwalled carbon nanotubes (MWCNTs), while the rest being non-reacted graphite and fullerenes. DTA curves show that combustion process of the nanotubes takes place in two stages, i.e., at 450 and 720 °C. At the lower temperature, combustion of MWCNTs occurs, while at higher one, fullerenes and non-reacted graphite particles burn. As-produced MWCNTs were used as electrocatalyst’s support materials and their performance was compared with that of traditional carbon support material Vulcan XC-72. MWNTs have shown almost twice higher real surface area, and electrocatalyst deposited on them showed better catalytic activity than corresponding one deposited on Vulcan XC-72.